(untitled) (Jurnal Teknologi (Sciences & Engineering), 2012)
Of all the microbial products manufactured commercially, antibiotics are the most important.Hundreds of antibiotics, a fraction of about 7000 antibiotics known so far, are commercially manufactured using microbial fermentation. In history, the first antibiotic discovered was used for controlling infections, but today more antibiotics are being used for other therapeutic applications. Being the most studied secondary metabolites through the history, antibiotics possess other pharmacological characteristics useful in the medical field. Therefore, the aim of this study is to present a review on antibiotics that include antibiotics definition, classification, mode of actions, uses, antibiotic resistance, side effects, type of antibiotics, metabolisms and determination methods of antibiotics.